(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
These days, customers expect a personalized experience, and conducting customer surveys has become a trend for seasoned and budding businesses. The establishment is still facing issues. One of those is a lack of marketing advertisements and campaigns, which is a worry for the restaurant. Despite being fully operational since January 2022, KP struggles to attract new customers. The lack of a marketing campaign and advertising is the most common problem that "KP" faces. Since "KP" only uses its Facebook page to advertise, "KP" missed the opportunity to offer promotions to all potential customers. This study concluded that by getting customers' feedback, we suggest that providing more information on the menu may help customers choose what they want to eat and ask what they think needs to be improved by knowing their purchase decision. Based on the collected data, it can be shown that the assessments of the aforementioned criteria of the two groups of respondents differ significantly from one another. It demonstrates that the null hypothesis is rejected since the t-value (3.38), which is smaller than the critical value (2.78), is rejected. It concludes that there is a significant difference between the customers' assessments of the two groups in terms of price, product, place, and promotion. The findings showed that all of the respondents had favorable opinions on their food, sales, and surroundings. Kain Peppers Resto firmly believes that there is an issue with their price, goods, location, and advertising. The responses from male and female respondents about these criteria, however, varied significantly. KP is aware that there are solutions to deal with the problem while also advancing their company. The researcher wants to help KP Resto develop a strong marketing plan. In order to make customers feel comfortable, we researchers advise firms to make it clear who is permitted entrance and to reinforce to all of their clients that discrimination is not accepted. We also recommend that restaurants offer delectable food at reasonable prices in a pleasant environment. Finally, we recommend that companies use advertising to attract more customers.